Puisi "Geometris" Kitab Ayub: Pengamatan terhadap Komposisi dan Struktur Kiastis Dialog Ayub dengan Teman-temannya (Ayub 3 - 26) - Aris Margianto (Theologia in Loco, 2018)
Amid the debate over the asymmetry of the structure of Job’s dialogue with his three friends - Eliphaz, Bildad and Zophar - and the tendency of OT experts to read it linearly, leading to conclusions about the process of redaction and the redactor of the book of Job, this paper shows that Job’s dialogue with His friends are arranged in a chiastic manner with a certain composition pattern based on the number of verses. Thereby supporting the opinion of the unity of the text of the book of Job.